DMRT2 Interacts With FXR and Improves Insulin Resistance in Adipocytes and a Mouse Model - Tao, Jing; Yu, Xiao-Lin; Yuan, Yu-Juan; Shen, Xin; Liu, Jun; Gu, Pei-Pei; Wang, Zhao; Ma, Yi-Tong; Li, Guo-Qing (Frontiers in Endocrinology, 2022)
Insulin resistance (IR) plays a critical role in cardiovascular diseases and metabolic diseases. In this study, we identified the downregulation of DMRT2 in adipose tissues from insulin-resistant subjects through bioinformatics analysis and in an insulin-resistant mouse model through experimental analysis. DMRT2 overexpression significantly attenuated HDF-induced insulin resistance and inflammation in mice. Moreover, in control and insulin-resistant differentiated mouse 3T3-L1 adipocytes, DMRT2 overexpression attenuated but DMRT2 knockdown enhanced the insulin resistance of 3T3-L1 adipocytes. DMRT2 interacted with FXR and positively regulated FXR level and transcription activity. In both control and insulin-resistant differentiated mouse 3T3-L1 adipocytes, FXR knockdown enhanced the insulin resistance and attenuated the effects of DMRT2 overexpression upon 3T3-L1 adipocyte insulin resistance. In conclusion, we identify the downregulation of DMRT2 in the insulin-resistant mouse model and cell model. DMRT2 interacts with FXR and improves insulin resistance in adipocytes.